Techno-Economic Analysis and CO2 Emissions of the Bioethanol-to-Jet Fuel Process - Park, Hyeon; Chae, Ho Jeong; Suh, Young Woong; Chung, Young Min; Park, Myung June (ACS Sustainable Chemistry and Engineering, 2022)
A model for the bioethanol-to-jet fuel process, based on ethanol dehydration, ethylene oligomerization, and hydrogenation, was developed to analyze its techno-economics and CO2emissions. A reactor model of ethanol dehydration with estimated kinetic parameters and experimental data-driven reactor models for oligomerization and hydrogenation were used for the process simulator. The techno-economic analysis of the process using the developed model showed that the total production cost (TPC) surpassed the total capital investment, and the bioethanol price contributed the most (approximately 75%) toward TPC with a normalized sensitivity of 0.80. The minimum selling price was calculated to be $119 per barrel, making the process only marginally profitable compared to the market price of $120 per barrel. However, the process was found to be environmentally friendly, exhibiting a negative value of net CO2emissions per unit mass of the product (-1.54 kg CO2equivalents/kg) after considering the biomass credit, indicating that CO2reduction was achievable. Further analysis demonstrated that the hydrogen production methods significantly influenced CO2emissions with a normalized sensitivity of 0.18.
Keywords: Bio-ethanols; Bioethanol-to-jet fuel; CO 2 emission; CO2 emissions; Ethanol dehydration; Ethylene oligomerizations; Process-models; Reactor modelling; Techno-Economic analysis; Total production cost; bioethanol-to-jet fuel; CO2emissions; ethanol dehydration; ethylene oligomerization; hydrogenation; process model; techno-economic analysis